Humanized Care From the Nurse–Patient Perspective in a Hospital Setting: A Systematic Review of Experiences Disclosed in Spanish and Portuguese Scientific Articles - Meneses-La-Riva, Monica Elisa; Suyo-Vega, Josefina Amanda; Fernández-Bedoya, Víctor Hugo (Frontiers in Public Health, 2021)
Nowadays, humanized care is an essential component in the field of health because the professional work of nursing seeks to provide quality services to patients who are suffering and fear illness or the dying process. Nurses recognize the need to incorporate humanized care into their daily work, as supported by Jean Watson, who states that caring entails establishing an adequate nurse–patient therapeutic relationship, where health education is a tool that promotes self-care in the patient, family, and community. The main objective of this work was to find scientific evidence on humanized care from the perspectives of nurses and hospitalized patients. To meet those research objectives, an exploratory systematic review of articles published in high-quality scientific journals from 2016 to 2020 using the PRISMA methodology in the Scopus and Scielo databases was conducted, yielding 26 studies that were analyzed. The findings show that nurses and patients perceive the need to remove the barriers that limit the advancement of humanized care in hospital institutions because they urgently demand that health professionals in all settings, especially critical ones, strengthen their humanizing role by sharing cordial, empathetic health experiences, and respecting their customs and beliefs during the hospitalization process. As a conclusion of the findings, the nurse–patient professionals agree that health personnel training is critical to providing humanized attention with quality in the hospital context, emphasizing that professional training should develop in practice soft skills, communication, safety environment, and human values.